Yardstick competition, privatization and company restructuring - Coutinho, Paulo; Mattos, César (Economia Aplicada, 2004)
One of the important devices to smooth the information asymmetry problem of the regulator is using "yardstick competition" The use of this mechanism has implications on the optimal division of a state-owned company before its privatization. We extend the framework introduced by Armstrong, Cowan and Vickers (1994) from 2 companies to n. The authors show that welfare increases when separating the company in two areas with two different owners compared to a monopoly. We extend this result and show that the combination of the regulators information gains and a decrease on uncertainty when a constant covariance of costs across areas is positive, results in gains from separating horizontally the companies before privatization. The introduction of scale economies turn the results ambiguous.